2011
DOI: 10.1080/00288233.2011.611148
|View full text |Cite
|
Sign up to set email alerts
|

The effect of breeding hoggets on lifetime performance

Abstract: The reported study involved mature ewes that had either been presented for breeding and had lambed as a hogget (MP), had been presented for breeding as a hogget but did not become pregnant (MNP) or were not presented for breeding as a hogget (NM). Their subsequent performance as mature ewes was examined. Although breeding as a hogget reduced (P B 0.05) two-tooth mating live weight and condition score in subsequent years, the differences were either smaller or not present at all (P !0.05). Breeding as a hogget … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…It has been reported that commercial farmers are concerned that hogget breeding results in increased risk of subsequent wastage; however, there was limited published data evaluating this [ 2 , 26 , 29 ]. In the present study, the association between hogget reproductive outcomes and subsequent wastage were evaluated for the Farm B cohort, as they were the only cohort that had both hoggets that were presented for breeding and hoggets that were not presented for breeding, and which did not cull any hoggets for poor reproductive performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that commercial farmers are concerned that hogget breeding results in increased risk of subsequent wastage; however, there was limited published data evaluating this [ 2 , 26 , 29 ]. In the present study, the association between hogget reproductive outcomes and subsequent wastage were evaluated for the Farm B cohort, as they were the only cohort that had both hoggets that were presented for breeding and hoggets that were not presented for breeding, and which did not cull any hoggets for poor reproductive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Hogget breeding can be utilized in pastoral sheep production systems to increase the number of lambs produced each year, while concurrently increasing lifetime productivity [ 26 , 27 , 28 ]. However, there is a common concern among commercial farmers that hogget breeding may reduce ewe longevity, thereby increasing ewe wastage [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservative farmers often delay the mating of young females until they are 18-24 months old. This is a complex problem, with a mix of sociological and biological causes and solutions: i) Sociological: a major driver of the decision to delay first mating in young females is the belief by farmers that mating young animals impairs their performance in subsequent years; research shows that this is not that case (Kenyon et al, 2004(Kenyon et al, , 2011(Kenyon et al, , 2014; ii) Biological: in young females, first conception is limited by nutrition and growth (live weight, condition score). It is important to focus on ensuring ovulation, conception and neo-natal survival, bringing us back to 'focus feeding', ultrasound, birth-site management; iii) Genetical: in young sheep, it has been shown that genetic selection can be used to increase growth rate and thus advance the onset of puberty, even if the extra growth is primarily muscle (Rosales et al, 2013ab, 2014.…”
Section: Early Mating Of Young Females (Management Of Puberty)mentioning
confidence: 99%
“…Replacement females can make up 25% of the breeding flock and their reproductive performance is generally lower than that of their flock mates (Quirke et al, 1977;Edwards et al, 2016). Additionally, replacement ewes that are successfully bred within their first year of age are more profitable and show greater lifetime reproductive performance than females bred to lamb at two years for the first time (Young et al, 2011;Kenyon et al, 2011;Kenyon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%